2017
DOI: 10.1371/journal.pntd.0005415
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mycobacterium ulcerans-specific T-cell cytokines for diagnosis of Buruli ulcer disease and as potential indicator for disease progression

Abstract: BackgroundBuruli ulcer disease (BUD), caused by Mycobacterium (M.) ulcerans, is the third most common mycobacterial disease after tuberculosis and leprosy. BUD causes necrotic skin lesions and is a significant problem for health care in the affected countries. As for other mycobacterial infections, T cell mediated immune responses are important for protection and recovery during treatment, but detailed studies investigating these immune responses in BUD patients are scarce. In this study, we aimed to character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…List of abbreviations not in text: Acyl carrier protein 2& 3(ACP2, ACP3); Acyltransferase with acetate specificity type 1 &2 (ATac1, ATac2); Acyltransferase with propionate specificity (ATp); Enoylreductase (ER); Ketoreductase type A and B (KRA, KR B); Ketosynthase type C (KS C); Ketosynthase domain (Ksalt), dehydratase (DH), and Phorbol 1-myristate 1-acetate (PMA) [34]. Cluster of differentiation 4 (CD4); CD 40 Ligand (CD40L); Tumor necrosis factor alpha (TNFα) [32].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…List of abbreviations not in text: Acyl carrier protein 2& 3(ACP2, ACP3); Acyltransferase with acetate specificity type 1 &2 (ATac1, ATac2); Acyltransferase with propionate specificity (ATp); Enoylreductase (ER); Ketoreductase type A and B (KRA, KR B); Ketosynthase type C (KS C); Ketosynthase domain (Ksalt), dehydratase (DH), and Phorbol 1-myristate 1-acetate (PMA) [34]. Cluster of differentiation 4 (CD4); CD 40 Ligand (CD40L); Tumor necrosis factor alpha (TNFα) [32].…”
Section: Resultsmentioning
confidence: 99%
“…A summary of these 12 studies are presented in Table 1. Nine out of the 12 CMI and/or serological studies identified were conducted in Africa, specifically Benin [14], Cameroon [31], Cote d'Ivoire [29], Zaire (now Democratic Republic of Congo, DRC) [27], Ghana [15,19,[30][31][32]34] and Uganda [27]. The remaining three studies, were conducted in Australia [8,26,28].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations